Transcription of a yeast telomere alleviates telomere position effect without affecting chromosome stability. - Sandell, L L (1994)
Telomeres are required for the stable maintenance of chromosomes in the yeast Saccharomyces cerevisiae. Telomeres also repress the expression of genes in their vicinity, a phenomenon known as telomere position effect. In an attempt to construct a conditional telomere, an inducible promoter was introduced adjacent to a single telomere of a chromosome such that transcription could be induced toward the end of the chromosome. Transcription toward two other essential chromosomal elements, centromeres and origins of replication, eliminates their function. In contrast, transcription toward a telomere did not affect the stability function of the telomere as measured by the loss rate of the transcribed chromosome. Transcription proceeded through the entire length of the telomeric tract and caused a modest reduction in the average length of the transcribed telomere. Transcription of the telomere substantially reduced the frequency of cells in which an adjacent URA3 gene was subject to telomere position effect. These results indicate that telomere position effect can be alleviated without compromising chromosome stability.